O efeito da marca na avalia????o de propagandas endossadas por celebridades. - Silva, Leonardo Aureliano da (2012)
The use of celebrity endorsement in advertising is common in many countries. The objective of this communication strategy is to influence consumer behavior in favor of an advertised product. Despite the fact that celebrity endorsement is an established technique, there are very few academic studies that explain the phenomenon of endorsements, even when they are performed with high and low congruence between the celebrity and the type of brand. In order to better understand this issue, we first performed a bibliographic study and subsequently went on empirical research, in which four experiments were conducted with different types of endorsements and brands. The data obtained through the sample, consisting of 713 individuals who had responded to the survey, were compiled and examined by variance analysis. Analysis of the results of the experiments show the following findings: a) in the absence of a brand, a celebrity contributes to a better evaluation of a product; b) a recognized brand is better assessed than an unrecognized brand, with or without a celebrity endorsement; c) an unrecognized brand is better evaluated when a celebrity with high congruence with the product is in the advertisement; d) a recognized and rejected brand is better evaluated than an unrecognized and rejected brand; e) a recognized and rejected brand can be better assessed if a celebrity with high congruence with the product is used in the advertising; f) an unrecognized and rejected brand is better evaluated when a celebrity with a high congruence is used; and g) celebrities with low congruence with the product tend to not to improve the evaluation of brands.